Korea Utara di Perang Rusia-Ukraina: Strategi Pengalihan Tensi Konflik di Semenanjung Korea - Waskito, Wasis; Genisa, Fathania Queen (Global and Policy Journal of International Relations, 2025)
The Trilateral agreement between South Korea, the United States of America, and Japan has escalated tensions in East Asia, particularly within the Korean Peninsula. Under escalated tension, North Korea strengthened military cooperation with Russia and supported the invasion of Ukraine by sending military troops and arms. This article analyzes that phenomenon to answer the question of why North Korea was willing to cooperate militarily in the middle of escalated tensions within the Korean Peninsula. Data was collected from primary sources, such as official documents, and secondary sources, such as news and academic articles. Through the lens of the balance of power, this article argues that North Korea has been trying to strengthen its manpower, obtain economic benefits, and divert the US' attention from Korean peninsula tension. North Korea used this tactic to prepare itself for potential conflict ahead.